The secret influence of the Moon : alien origins and occult powers - Proud, Louis. frey50
"The Moon is not a cold, dead rock but a rich, fascinating world just as alive as Earth"--Provided by publisher.
The Moon That We Know -- A Closer Look at the Moon -- Origin Unknown -- The Mystery Deepens -- Our Relationship with the Moon -- The Moon Matrix -- Food for the Moon -- Life on the Moon -- The Lunar Sphere.
Keywords: Moon; Human beings -- Effect of the moon on; Moon -- Origin; Extraterrestrial beings; Occultism